Success of pacemaker remote monitoring using app‐based technology: Does patient age matter?. Issue 10 (21st August 2018) - Tarakji, Khaldoun G.; Vives, Carola Alfaro; Patel, Amisha S.; Fagan, Dedra H.; Sims, J. Jason; Varma, Niraj
Abstract: Background: Remote monitoring (RM) improves patient outcomes. App‐based RM is a novel technology that enables transmission of implantable device data using smart devices. Limited data exist on the impact of age and sex on the use of app‐based RM. Objective: To examine the impact of age and sex on the proportion of pacemaker patients who activated app‐based RM, time from order to activation, and patient follow‐up transmission adherence per guidelines. Methods: A retrospective analysis was performed using deidentified data from U.S. pacemaker patients enrolled in the Medtronic CareLink database with an app‐based monitor (MyCareLink Smart™). Activation was defined as first RM transmission and was considered early if it occurred < 90 days from order. Adherence analysis was limited to patients with ≥12 months' follow‐up from activation and excluded transmissions < 90 days from activation. Results: Of 48, 016 patients assigned app‐based RM, 40, 511 (84.4%) activated their device; of these, 31, 640 (65.9%) activated their device early. Among 14, 232 activated patients (with 12 months' follow‐up), 12, 743 (89.5%) were considered adherent to guidelines by transmitting at least once more within 3–12 months following their activation transmission. While there were statistical differences in activation, early activation, and adherence among age and sex groups due to large sample sizes, the differences were not clinically significant and the majority of older patients were able to successfully use app‐based RM. Conclusions: Most patients in this large and first‐of‐its kind reported cohort used smart devices to successfully activate app‐based RM technology and remained adherent per guidelines irrespective of age or sex.